Peningkatan Kompetensi Digital Marketing UKM Melalui Pelatihan Video Promosi Untuk Komunitas UKM Kelurahan Pandean Lamper Kota Semarang - Natalia Sari Pujiastuti; Kharisma Ayu; Sri Syamsiah (Universitas 17 Agustus 1945 Semarang, 2023)
This research highlights significant changes in consumption patterns and digitalization that pose challenges for businesses that are unable to adapt to these changes. Data shows that the majority of SMEs in Indonesia have not yet entered the digital ecosystem, one of which is business actors who are members of the Pandean Lamper Village SME Community. Therefore, promotional video training using the CapCut application is a strategic solution. This application is popular, free, and has complete features. Against this background, the research explores how to improve the digital marketing competence of SMEs through promotional video training. Aims to provide knowledge and skills to SMEs in digital marketing, so that they can utilize social media and video to promote their products. The benefits include increasing sales turnover for SMEs and contributing to academic development at Semarang University. This activity was attended by 28 people, with an age range of 25 – 60 years, the majority of whom are business people in the culinary sector. From the results of these activities, participants felt the benefits and were willing to persist in participating in the training activities until completion.